The Effect of Faba Growing Media and Cow Manure on the Growth and Yield of Mustard Greens (Brassica juncea L.) - Novi Aziz; Juandi Ananda; Irfan Habib Maulana; Ledi Andras; Fiana Podesta; Nurwiyanto Nurwiyanto (Universitas Muhammadiyah Sidoarjo, 2023)
The aim of the study was to determine the effect of FABA growing media and cow manure on the growth and yield of mustard greens (Brassica Juncea L.). This research was carried out on the land of the Bengkulu Muhammadiyah University. The design used was a factorial complete randomized design (CRD) with 1 factor, namely factor A1 = 4:1 (Faba 100 %), A2 = 3:1 (Faba 75 % + Manure 25%) A3 = 2:2 (Faba 50 % + Manure 50 %), A4 = 1:3 (Faba 25 % + Manure 75 %), A5 = 0:4 (Manure 100 %). Based on the tested level of one of these factors, 20 treatment combinations were obtained. Each experimental treatment contained 5 plants so that there were 100 plants to be observed in this study. The results of this study showed that there was an interaction between the treatment of Faba growing media and cow manure on plant height, leaf width, leaf length, number of leaves and dry weight of mustard plants. The best results were in the treatment interactions between A1, A2, A3, A4, and A5, the best growth was in the A3 and A4 treatments. Because, in the 100% and 75% Faba treatment, plant growth was not good and there were several plants with yellowing leaves. This indicates that the use of Faba planting media must be balanced with organic matter so that plant growth is maximized.